Helix (Cornu) aspersa (O.F. Müller, 1774) (Gastropoda: Helicidae) in the Czech Republic - Lucie Juřičková; Filip Kapounek (Malacologica Bohemoslovaca, 2009)
The living hibernating population of non native species Helix (Cornu) aspersa was found for the first time in the Czech Republic.